Template Matching dalam Otomatisasi Penghitung Sel Keping Darah Berbasis Image Processing untuk Deteksi Dini Derajat Penyakit Demam Berdarah - Amelia Yolanda -; Deddy Prayama -; Aulia Ramadhani - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2018)
One of the diseases that can be detected through blood tests is Dengue Hemorrhagic Fever (DHF). The number of platelets are one of the guidelines used by doctors diagnosing DHF. Actually, platelets can be calculated manually, but it will be very difficult if the platelets are counted quite a lot. So, we need a technology that can calculate the number of platelets quickly and automatized to get more accurate results. The automatic systems built by using the template matching method with image processing include HSL Segmentation with Luminance type and Reverse Color Manipulation. After building the system, the system will automatically look for objects that match the template in the sample image and then give the marking and calculate it.The overall system testing results are the number of platelets which are then classified manually at what degree of DHF.